English Proficiency of Icelandic and Immigrant Children - Maltseva, Elena, 1977- (2009)
The student population in Iceland is becoming culturally and linguistically more diverse. The goal of this study was to find out whether there is a discrepancy in English proficiency between Icelandic and immigrant learners; if so, what the possible reasons for it are; and whether teachers use the same or different strategies with the two groups of students. The data were gathered by means of surveys of two groups of subjects, students and teachers. The first group consisted of sixteen Icelandic and fifteen immigrant English language learners from the tenth grade in two primary schools in Reykjavik. The second group included twenty-five teachers of English. The findings indicate that there is a discrepancy in English proficiency between Icelandic and immigrant learners. The results also suggest that the majority of the teachers who responded do not receive specific assistance in teaching English as a foreign language to immigrant learners, and therefore more than half of them use the same teaching strategies for both groups of students.